ANALYSIS OF STRENGTH AND PROMOTION ON CUSTOMER PURCHASING DECISIONS THROUGH CUSTOMER ENGAGEMENT IN FUTURE MSME’s - Toruan, Rade Juliman Lumban; Sembiring , Beby Karina Fawzeea; Lubis, Arlina Nurbaity (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
The purpose of this study is to determine directly and indirectly the relationship between strength and promotion on customer purchasing decision through customer engagement. The population in this study are MSE consumers in Medan City, the number of which cannot be known with certainty. The sample withdrawal used is purposive sampling with a classification, namely the general public who buy food from food stalls or home catering, consumers who buy clothes from small boutiques or online stores on social media, and consumers who use laundry services or home salons. The research sample was taken using the Zikmund formula so that a sample size of 100 respondents was obtained. Data analysis was carried out using structural equation modeling (SEM) techniques with Smart-PLS analysis tools to test the direct and indirect relationships between these variables. The results explain that strength directly has a significant effect on customer engagement, promotion directly has a significant effect on customer engagement, strength directly has a significant effect on customer purchasing decisions, promotion directly has a significant effect on customer purchasing decisions, customer engagement directly has a significant effect on customer purchasing decisions, strength indirectly has a significant effect on customer purchasing decisions through customer engagement, and then promotion indirectly does not have a significant effect on customer purchasing decisions through customer engagement.